Constitutional democracy and constitutional adjudication: a comparison of constitutional adjudication institutions in Malaysia and Indonesia - Mokhtar, Khairil Azmin; Satriawan, Iwan; Islami, Muhammad Nur (2016)
The experience of some countries show that parliamentary sovereignty creates problems of hegemony of majority which has the potential to ignore minority. One of democratic responses to the evil of the majority is the emergence of the concept of constitutional democracy. The tyranny of majority against the rights of the minority is warded off by constitutional safeguards enforced primarily by the court. This is one of the reasons why Malaysia and Indonesia adopt the doctrine of constitutional supremacy when they achieved independence in 1957 and in 1945 respectively. In spite of close proximity in terms of territory and sharing cultural and historical heritages the two countries have fundamental structural constitutional differences. This paper aims at comparing constitutional adjudication as one of the mechanisms of constitutional democracy in both countries. The establishment of the Indonesian Constitutional Court in 2003, and the functions of the superior courts in Malaysia are part of realizing the goal of the rule of law state and democracy. The courts have the objectives of striving for a dignified life of the nations, and perform as actors of exercising judicial review. The courts in both countries play the role as check and balance mechanisms of the main organs in their constitutional and political systems. Each country has a different model of constitutional adjudication. Malaysia follows the common law model which functions the superior courts as organs of the constitutional adjudications, while Indonesia follows kelsenian model by establishing a separate new court, namely the Constitutional Court. This paper intends to observe the establishment, role and power of constitutional adjudications institutions of both countries. The development and experiences of the institutions in both countries not only shed more lights of constitutional democracy within the two countries, (but also influenced) the process of democratic consolidation in the region.